Mess Project Construction Cost Analysis Using SNI 2013 and AHSP Methods - Tamba, Dewi Fortuna; Indrastuti (Journal of Civil Engineering and Planning (JCEP), 2024)
The budget calculation is one of the most important aspects in a construction project, beside time and qualities. There are several methods that we can use to estimate how much material is needed, including SNI 2013 and AHSP method. However, these 2 methods have to be implemented meticulously to reduce overbudget and material wastage.  The data come from the list of working items that is used as a bid by the company owner, the standard given by the project manager, and items price list of each working part. The purpose of this research is to compare and find which method is the most effective in controlling the project expenditure. Also, researcher will explained how to calculate data as well as the advantage and weakness of both methods that have been mentioned above.